Entrepreneurial Competencies for Managing Business in Informal Economy: A Study of B40 Women Entrepreneurs in Malaysia - Noor, Nurul Hidayana Mohd; Zaini, Syeliya Md; Omar, Noralina; Beta, Raja Mayang Delima Mohd; Wei, Chang Lee (Journal of Accounting, Business and Management (JABM), 2024)
Globally, the lack of participation among women in entrepreneurship is credited to a series of factors, including a lack of education, inadequate competencies, gender stereotypes, and inadequate access to resources. This study aims to assess the current competencies level of women entrepreneurs in the informal economy in Malaysia. The informal economy—also referred to as the shadow economy- is far more significant than the formal economy and a way of livelihood for many people in most developing countries. Second, this study aims to discover the skills and knowledge required by women entrepreneurs. This study employed a qualitative research approach and purposive sampling technique where 20 women entrepreneurs were selected as key informants. This study only focuses on women entrepreneurs from B40 groups in Kuala Lumpur with more than one year of business experience and involved in informal businesses such as street vendors, hawkers, and home-based businesses. The interviews were analysed using thematic analysis. The study first found that most informants have limited business management competencies. The findings also have categorized the main competencies needed into seven main themes, namely, 1) communication, 2) strategic management, 3) financial management, 4) product innovation, 5) ICT skills, 6) time management, and 7) customer relationship management.